First contribution to the genus Gymnopilus (Agaricales, Strophariaceae) in Paraguay - Campi Gaona, Michelle Geraldine (2021)
Gymnopilus is characterized by its ferruginous-yellow basidiomata and lamellae, ferruginous spore print, ellipsoidal basidiospores with warty and rough ornamentation, and lacking a germinative pore. Here, novel data on the Gymnopilus species of Paraguay is presented, macro and microscopic morphological characteristics, distribution, and ecology are described, and a taxonomic discussion is provided. Gymnopilus imperialis is recorded in the Alto Paraná Department, G. lepidotus in the Central Department, G. luteofolius in the Cordillera Department, G. peliolepis in the Paraguarí Department, and G. purpureosquamulosus in the Central Department and Boquerón, all as new records for Paraguay. Photographs of the fresh basidiomata and some microscopic structures such as basidia and basidiospores are attached.